PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PRAKARYA DAN KEWIRAUSAHAAN SISWA PADA MATERI KONSEP DASAR KERAJINAN DI SMK YKTB 2 BOGOR - Kusnadi Kusnadi (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
THE APPLICATION OF JIGSAW TYPE COOPERATIVE LEARNING MODELS TO IMPROVE RESULTS OF CRAFTSMANSHIP AND ENTREPRENEURSHIP STUDENT IN BASIC CRAFTS CONCEPT MATERIALS IN SMK YKTB 2 BOGORThe Jigsaw cooperative model is one of the learning models that teachers can apply in Craft and Entrepreneurship learning to provide meaningful learning experiences for students because it can generate teaching and learning activities. Positive student learning activities are a process for students to learn and understand the material. The more often students involve actively in teaching and learning activities, the greater the opportunity for students to develop their abilities both academically to achieve the KKM targets (Minimum Completeness Criteria) and also hopefully in terms of developing attitudes in students. The research method used is classroom action research. This research was conducted on students of Class XI OTKP 1 SMK YKTB 2 Bogor. With 34 students consisting of 17 boys and 17 girls. The correctness of the action hypothesis and to answer research questions need to be supported by accurate data and information obtained through research. The data were obtained through daily tests carried out at the end of the cycle, individual assignments in the form of homework (PR) group assignments, observation sheets and student questionnaires. Based on the analysis of the research data, it can be seen that the application of the jigsaw cooperative model in learning integers can improve student learning outcomes and student activity has increased because all students feel valued and can take part in maintaining the good name of their group even though their score is not 100 which is important in Each cycle test has an increase, so that students give a positive response to the jigsaw cooperative learning model.